2006
DOI: 10.1245/s10434-006-9192-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CA125 in Patients with Peritoneal Mesothelioma Treated with Cytoreductive Surgery and Intraperitoneal Hyperthermic Perfusion

Abstract: CA125 was elevated in the majority of patients with PM in the present series. Serial maker measurements paralleled tumor growth or regression after CRS and IPHP, suggesting the need of further studies to assess the role of CA125 in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 30 publications
2
52
1
2
Order By: Relevance
“…In the present case, since the tumor had already metastasized to the liver and abdominal lymph nodes at the time of diagnosis, we chose systemic chemotherapy (CDDP plus PEM) rather than a combination of cytoreductive surgery and intraperitoneal chemotherapy, but unfortunately it was ineffective. In fact, the serum levels of CA125 and hyaluronic acid, which were previously reported to be useful for monitoring the effectiveness of therapy, increased gradually during the clinical course after the introduction of systemic chemotherapy (14,15). SMRP was recently identified as a potential serum marker of malignant mesothelioma, and has also been shown to be useful for monitoring disease progression (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, since the tumor had already metastasized to the liver and abdominal lymph nodes at the time of diagnosis, we chose systemic chemotherapy (CDDP plus PEM) rather than a combination of cytoreductive surgery and intraperitoneal chemotherapy, but unfortunately it was ineffective. In fact, the serum levels of CA125 and hyaluronic acid, which were previously reported to be useful for monitoring the effectiveness of therapy, increased gradually during the clinical course after the introduction of systemic chemotherapy (14,15). SMRP was recently identified as a potential serum marker of malignant mesothelioma, and has also been shown to be useful for monitoring disease progression (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of serum tumour markers has been underlined. In patients with peritoneal mesothelioma, we reported a sensitivity rate of 100% (12/12) for CA125 in assessing disease progression after complete CRS and HIPEC [46] In patients with pseudomyxoma peritonei with positive baseline values, marker concentrations at progression were elevated in 24 of 29 (82.7%) patients for CEA, in 18 of 22 (81.8%) patients for CA19.9, in 12 of 19 (63.1%) patients for CA125, and in 4 of 6 (66.7%) patients for CA15.3 [47] . Van Ruth reported that CEA normalized in 73% patients and CA19.9 in 57% patients with preoperative increased levels, and that CA19.9 was positive in 14 of 14 cases of relapsing PMP with elevated preoperative levels [48] .…”
Section: Long Term Follow-upmentioning
confidence: 98%
“…Most of the research on serum markers have been done in pleural mesothelioma, with some patients shown to have elevations in CA-125, alpha fetoprotein, CEA, mesothelin, osteopontin, and fibulin-3. Unfortunately, their sensitivities are too low to be used for diagnostic purposes (28,(33)(34)(35). Levels of serum mesothelinrelated protein (SRMP) have shown more promise, with a sensitivity of 60% (7,36).…”
Section: Diagnosismentioning
confidence: 99%
“…While not useful for diagnostic purposes in MPM, CA-125 and mesothelin have some promise for a marker of tumor response or surveillance. If initially elevated, serum CA-125 often normalizes to baseline levels after treatment and has been shown to correlate with post-treatment disease progression (33).…”
Section: Diagnosismentioning
confidence: 99%